Paleohydrology based on sedimentology on Dasht e Arzhan basin SW Iran - zahra sadat Hoseini; shahriar khaledi; Abdolmajid Naderi Bani (تحقیقات کاربردی علوم جغرافیایی)
Paleo-climate reconstructions based on multi-proxy such as sedimentology is current in climatology investigation. In this way, National Institute of Oceanography and Atmospheric Science cored 960cm from Arzhan wetland SW of Iran than we have investigated of sedimentology. Primarily the core was measured on magnetic sensibility per 1cm and secondly was subsampled according to magnetic sensibility and were analyzed include TOC, CaCO3, and Grading laser and etc. Finally four samples of pace of plant were selected and have been dated in carbon 14 dating laboratory of Poznan, Poland, and calibrated trough of core based on Calib rev. 7.1. Dating have determined that core had covered 15000 Cal. BP. According to this investigation, we obtained 5 period of climate conditions during Pleistocene to Holocene in this area. 15000-13000 Cal. BP. Late Pleistocene climate conditions were colder and wetter period that indicate end of the Ace age.  13000-11000 Cal. BP. Climate begin to warmer and dryer. 11000-9000Cal.BP. because of this period shows many fluctuations in all proxies we named this period to the period of transfer from ace age to interglacial period. 9000-7000Cal. BP there have been warm and cold conditions compare to late Holocene. 7000- Present indeed in this period radiantly modern pattern of atmospheric circulation has been performed due to all of proxies in late Holocene begin to fixed on the same pattern. So probably atmospheric circulation from meddle Holocene begin to get harmonic to present. Any way for determinate of paleo-climate in this area we need to use of multi proxy investigation in area.